FINE MOTOR SKILLS IN CHILDREN WITH DOWN SYNDROME - Memišević, Haris; Mačak, Amra (Specijalna edukacija i rehabilitacija, 2015)
Fine motor skills are very important for children’s overall functioning. Their development is necessary for many everyday activities such as dressing, feeding, holding objects etc. Moreover, fine motor skills are also correlated to the childrens’ academic success at school. Recent research suggests close relationship between motor skills and intelligence. Given the relative paucity of literature on fine motor skills in different etiological groups of children with intellectual disability (ID), we examined these skills in children with Down syndrome. The sample for this study comprised 90 children with ID, aged 7-15, who belonged in three etiological groups: 1. Down syndrome, 2. Organic/other genetic cause of ID and 3. Unknown etiology of ID. Fine motor skills were assessed with the Purdue Pegboard Test. The results of this study indicate that children with Down syndrome did not differ statistically significantly from the other two etiological groups. On the other hand, children with unknown etiology of ID performed statistically better than children with organic/other genetic cause of ID. An additional goal was to examine the fine motor skills in children with Down syndrome in relation to the child’s sex. There were no statistically significant differences in fine motor skills between girls and boys with Down syndrome. It is important to provide children with Down syndrome, and all other children with ID, with early (re)habilitation programs for the improvement of their fine motor skills. Special educators and rehabilitators should play a crucial role in the assessment and in creating programs for the development of these skills.